Front Cover. Issue 2 (27th January 2020) - Khoury, Colin K.; Carver, Daniel; Barchenger, Derek W.; Barboza, Gloria E.; van Zonneveld, Maarten; Jarret, Robert; Bohs, Lynn; Kantar, Michael; Uchanski, Mark; Mercer, Kristin; Nabhan, Gary Paul; Bosland, Paul W.; et al.
Abstract : The cover image is based on the Original Article Modelled distributions and conservation status of the wild relatives of chile peppers (Capsicum L.) by Colin K. Khoury et al., https://doi.org/10.1111/ddi.13008 .